Upper midline incision for living donor right hepatectomy. Issue 9 (9th July 2016) - Singh, Manoj K.; Lubezky, Nir; Facciuto, Matias; Contreras‐Saldivar, Alan; Wadhera, Vikram; Arvelakis, Antonios; LaPointe‐Rudow, Dianne; Florman, Sander; Facciuto, Marcelo E.
Abstract: Background: Living donor liver transplantation is a viable option to increase access to transplantation and techniques to limit the operative incision is one way to increase donation by decreasing donor morbidity. We describe our experience with a limited upper midline incision (UMI) for living donor right hepatectomy. Study Design: Prospective data were collected on 58 consecutive living liver donors who underwent right hepatectomy via a UMI. Results: Donor median age was 32 years, with median body mass index of 24.6. The mean incision length was 11.7 cm. Ten liver grafts included middle hepatic vein. The mean graft volume by preoperative imaging was 940 cc. The mean operative time was 407 minutes; cellsaver was utilized in 35 patients with median of 1 unit. Mean peak aspartate transaminase (AST) and alanine transaminase (ALT) were 492 and 469, and peak bilirubin and international normalized ratio (INR) were 3.3 and 1.8. The average length of stay was 6 days. There were 10 Clavien grade I and 11 Clavien grade II complications. Three patients developed an incisional hernia requiring surgical repair. Conclusion: Living liver donor hepatectomy can be safely performed through a UMI. This approach consolidates the steps of liver mobilization, hilar dissection, and parenchymal transection in a single‐exposure technique, with incision comparable to the laparoscopic‐assisted modality.